2011
DOI: 10.1016/j.joca.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Hip muscle weakness in patients with symptomatic femoroacetabular impingement

Abstract: Patients with symptomatic FAI presented muscle weakness for all hip muscle groups, except for internal rotators and extensors. Based on EMG recordings, it was demonstrated that patients with symptomatic FAI have a reduced ability to activate TFL muscle during hip flexion. These findings provide orthopedic surgeons with objective information about the amount and specificity of hip muscle weakness in patients with FAI. Future research should investigate the relationship between hip muscle weakness, functional di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
245
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(261 citation statements)
references
References 39 publications
9
245
1
6
Order By: Relevance
“…The pattern for protective tone may be categorized into the Lower Cross Syndrome as described by Janda [44] or adductor tone in response to hip pain and inhibition of primary hip stabilizers which is clinically consistent in this group of patients. As described previously, Green demonstrated the extensive function of the adductor group [38]. Therefore, it is understandable that in the presence of pain, the adductor group would respond to assist in protection and stabilization.…”
Section: Treatment By Layersupporting
confidence: 56%
See 1 more Smart Citation
“…The pattern for protective tone may be categorized into the Lower Cross Syndrome as described by Janda [44] or adductor tone in response to hip pain and inhibition of primary hip stabilizers which is clinically consistent in this group of patients. As described previously, Green demonstrated the extensive function of the adductor group [38]. Therefore, it is understandable that in the presence of pain, the adductor group would respond to assist in protection and stabilization.…”
Section: Treatment By Layersupporting
confidence: 56%
“…The mechanism may be acute, traumatic, overuse tendinosis or developmental avulsions [37]. Casartelli et al [38] report that patients with FAI presented with decreased maximal voluntary contraction levels for the hip adduction (28%), flexion (26%), external rotation (18%) and abduction (11%) when compared with the control group, demonstrating the contractile dysfunction occurring as a result of structural pathology and pain. The tensor fascia lata (TFL) also demonstrated decreased activation during hip flexion in the hip diagnosed with FAI.…”
Section: Layer Iii: Contractile Layermentioning
confidence: 99%
“…While the tensor fasciae latae muscle is less commonly injured than the other hip abductors [17], a recent report using electromyographic recordings showed that patients with symptomatic femoroacetabular impingement had a reduced ability to activate the tensor fasciae latae muscle during hip flexion [18], showing that the tensor fasciae latae can undergo changes due to a different weight loading.…”
Section: Discussionmentioning
confidence: 99%
“…Since lateral balance is controlled by coordinated hip muscle activity and trunk movement (12), reduced hip muscle strength (13,14) and limited hip joint range of motion (ROM) observed in those with hip OA may contribute to impaired balance control. Importantly, younger individuals with hip pathol-ogy also exhibit reduced hip strength and ROM (15), which may render these individuals at risk of impaired balance control.…”
Section: Introductionmentioning
confidence: 99%